Bother Associated with Climacturia After Radical Prostatectomy: Prevalence and Predictors. Issue 4 (21st January 2020) - Salter, Carolyn A.; Bach, Phil Vu; Miranda, Eduardo; Jenkins, Lawrence C.; Benfante, Nicole; Schofield, Elizabeth; Nelson, Christian J.; Mulhall, John P.
Abstract: Introduction: Orgasm-associated incontinence, climacturia, is one of the lesser studied radical prostatectomy (RP) complications. Little is known about patient bother related to this condition, specifically, its prevalence and predictors. Aim: To ascertain the prevalence and predictors of patient bother associated with climacturia. Methods: Patients presenting for the evaluation of sexual dysfunction after RP at a single center were queried on various domains of sexual dysfunction. This included orgasmic dysfunction and sexual incontinence (including climacturia and arousal incontinence). Patients were specifically asked about the frequency and amount of climacturia. In addition, questions addressed patient bother and the perceived bother of their partners. Descriptive statistics were used for patient characteristics. A t-test was used for comparing the frequency of patient and partner bother, and the Pearson correlation test compared relationships between bother and predictors. Multivariable analysis was conducted to define predictors of climacturia-associated bother. Main Outcome Measure: The main outcome measures was the prevalence and predictors of climacturia-associated patient bother and perceived partner bother. Results: Climacturia was reported by 23% of 3, 207 consecutive men analyzed. Bother of any degree was experienced by 45% of these patients, and 14% reported partner bother related to this condition. Patient bother was associated with perceived partner bother ( P < .001) and inversely correlated with relationship duration ( P < .001). The overall frequency and quantity of climacturia were also predictive ( P < .001 for both). In the adjusted model, all of these factors remained significant. Clinical Implications: Given the prevalence of this condition and the bother associated with it, this complication should be discussed with patients preoperatively. Strength & Limitations: Strengths include a large study population and specific questions on climacturia-associated bother. Limitations include the fact that it is a single-center study and no direct partner questioning occurred. Conclusion: Climacturia and its associated bother are common after RP. The predictors of patient bother include perceived partner bother, shorter relationship duration, and increasing frequency and quantity of climacturia.